Pengaruh Produksi Beras, Harga Beras, dan lam Negeri Terhadap Impor Beras di Provinsi Sumatera Utara - Rindah Sari; muhammad sahnan; zulkifli Siregar (Universitas Islam Sumatera Utara, 2022)
This study aims to determine the effect of Rice Production, Rice Consumption, Domestic Rice Prices, Foreign Rice Prices, Exchange Rates and Rice Stocks either partially or simultaneously on Rice Imports in Indonesia. The data are sourced from the Central Statistics Agency (BPS), Bank Indonesia, and the International Rice Research Institute (IRRI). The results of the partial significance test show that the rice production variable has an insignificant negative effect on the variable amount of rice imports. The price of rice has an insignificant negative effect on the variable amount of rice imports, the price effect on rice imports is not significant because rice is a staple item that people want or not to continue to consume, the variable rice consumption has a positive and insignificant effect on the variable amount of rice imports. Simultaneous significance test is known that rice production, rice price and rice consumption variables simultaneously have no significant effect on the variable amount of rice imports because the probability value is value. It is necessary to understand that North Sumatra has many rice granaries, although North Sumatra has to import rice, this is only temporary, for example before religious celebrations or when some rice granaries experience crop failure. The results of the determination test showed that variations in rice production variables, rice prices and rice consumption had an effect of 30.4% and the remaining 69.6% were influenced by other variables that were not examined, such as climate change which made North Sumatra fail to harvest and lack of rice stocks, increased demand. North Sumatran rice on religious holidays such as Eid and New Year, the rupiah exchange rate against foreign currencies, population, North Sumatra's per capita income, and others.